Thyroidectomy in dogs with thyroid tumors: Survival analysis in 144 cases (1994‐2018). (27th February 2023) - Enache, Daniela; Ferro, Livia; Morello, Emanuela M.; Massari, Federico; Romanelli, Giorgio; Nicoli, Stefano; Guazzetti, Stefano; Porporato, Federico; Zini, Eric
Abstract: Background: Few studies have assessed predictors of outcome in dogs with thyroid tumors undergoing thyroidectomy. Objective: To estimate the survival and identify prognostic factors in dogs with thyroid tumors treated by thyroidectomy. Animals: A total of 144 client‐owned dogs with thyroid neoplasia that underwent thyroidectomy. Methods: Retrospective study. Data for analysis included hospital attended and year of surgery, signalment, thyroxine concentration, thyroid tumor features (lobe involvement, size, invasiveness, histopathological type), thrombosis, metastasis, additional surgery and therapy, administration of adjuvant chemotherapy. The association of predictors with survival (time from surgery to death) were assessed by calculating cause‐specific hazard ratios (HRcs ) and 95% confidence intervals (CI). Causes of death were classified as thyroid‐related or because of other cause. Results: Overall median survival time was 802 days (CI95% = 723‐1015 days); 89 dogs (77.4%) survived >500 days. Metastases were identified at admission in 12 (8.3%) dogs and were associated with higher thyroid cancer‐related fatality (HR = 5.83, CI95% = 1.56‐21.78; P = .009). Thrombosis occurred in 40 dogs and was associated with increased risk of death because of other cause (HR = 2.73, CI95% = 1.18‐6.35; P = .019). Nonfollicular carcinoma (HR = 4.17, CI95% = 1.27‐13.69; P = .018) and administration of chemotherapy (HR = 3.45, CI95% = 1.35‐8.82; P = .01) were associated with higher risk of thyroid cancer‐related death. Conclusions and Clinical Importance: Dogs with thyroid tumors undergoing thyroidectomy have a long life expectancy. Despite the rare presence of nonfollicular carcinoma and metastases, thyroidectomy should still be considered in some of these dogs.